PERAN KEAMANAN KERJA DAN KOMITMEN ORGANISASI TERHADAP TURNOVER INTENTION SERTA DAMPAKNYA PADA KINERJA KARYAWAN - Soedarmadi Soedarmadi; Nisa Novia Avien Christy; Dyah Handayani Dewi (Universitas Semarang, 2017)
A preliminary survey that was conducted shows that in 2013, the turnover rate of employees of PT Indotirta Jaya Abadi reach the number of 9,3%. Turnover intention may lead to a worsening of the employee performance. Therefore, it is necessary to examine the factors affecting turnover intention so that management will be able to push it down.To answer the problem, a model is developed for this empirical research with four observed variables, i.e.: job security, organizational commitment, turnover intention, and employee performance. There are five hypotheses proposed in this research. Primary data is obtained by distributing questionnaires to the employees of PT Indotirta Jaya Abadi. There are 128 data to be studied with Structural Equation Modeling Analysis Method.The result of the hypotheses test according to the Critical Ratio and the probability value shows that job insecurity has negative significant effects on turnover intention, organizational commitment has negative significant effects on turnover intention, turnover intention has negative significant effects on employee’s performance, job insecurity has positive not significant effects on employee’s performance, and organizational commitment has positive not significant effects on employee’s performance.